The Impact of Advances in Molecular Genetic Pathology on the Classification, Diagnosis and Treatment of Selected Soft Tissue Tumors of the Head and Neck - García, Joaquín J. (Humana Press Inc, 2010)
Recent advances in molecular pathology have had a significant impact on the diagnosis, classification, and treatment of soft tissue tumors. The practical application of these discoveries promises to assist greatly in the evaluation and treatment of soft tissue neoplasms in the head and neck region—an area characterized by exceedingly complex anatomy that often restricts the ample sampling of lesions and complete surgical resection. This reviews details some ways in which molecular techniques have strengthened conventional diagnostic and management approaches to low-grade fibromyxoid sarcoma, angiomatoid (malignant) fibrous histiocytoma, and dermatofibrosarcoma protuberans, all of which may involve the head and neck region.